1993
DOI: 10.1016/0022-3115(93)90034-v
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation assisted stress corrosion cracking of controlled purity 304L stainless steels

Abstract: The effect of chromium, phosphorus,, silicon and sulfur on the stress corrosion cracking of 304L stainless steel in CERT tests in high purity water or argon at 288°C following irradiation with 3.4 MeV protons at gl0*C to 1 dpa, has been investigated using ultrahigh pur:ty alloys (UHP) with controlled impurity additions. Grain boundary segregation of phosphorus or silicon due to proton irradiation was quantified using both Auger electron spectroscopy and scanning transmission electron microscopy, and the alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…This work used Ni-ion and proton irradiation to study the effects of misfit elements, Hf and Pt, on the radiation-induced microstructure in alloys 316SS. Heavy-ion and proton irradiations are used due to the advantages that previous experience demonstrated that these irradiations could effectively produce similar radiationinduced microstructure and microchemistry relevant to LWRs at around 300°C [9][10][11][12][13][14]. The use of heavy-ion and proton irradiation in this work also distinguishes whether the major effect of the solute additions is on cascade processes or isolated point defect kinetics during the development of irradiated microstructure.…”
Section: Introductionmentioning
confidence: 98%
“…This work used Ni-ion and proton irradiation to study the effects of misfit elements, Hf and Pt, on the radiation-induced microstructure in alloys 316SS. Heavy-ion and proton irradiations are used due to the advantages that previous experience demonstrated that these irradiations could effectively produce similar radiationinduced microstructure and microchemistry relevant to LWRs at around 300°C [9][10][11][12][13][14]. The use of heavy-ion and proton irradiation in this work also distinguishes whether the major effect of the solute additions is on cascade processes or isolated point defect kinetics during the development of irradiated microstructure.…”
Section: Introductionmentioning
confidence: 98%
“…[10] Austenitic stainless steel (SS) core internal components are susceptible to irradiation-assisted stress corrosion cracking (IASCC) during service in nuclear power plants' light water reactors. [11][12][13] One of the effects of irradiation is the hardening of the SS due to modifications in the dislocation distribution in the alloy. [14,15] Irradiation also alters the local chemistry of these austenitic alloys, for example, in the vicinity of grain boundaries by a mechanism of radiation-induced segregation.…”
Section: A Behavior Of Ferritic and Austenitic Steels In Light Watermentioning
confidence: 99%
“…Note the excellent correlation between 1 dpa proton irradiation data and the 1.1 dpa neutron data. Finally, we have consistently observed that proton irradiation, under the same conditions as neutron irradiation, causes IASCC susceptibility in austenitic stainless steel [10]. Figure 2.13…”
Section: Proton Irradiationmentioning
confidence: 55%